IMPLEMENTASI KONSEP KELUARGA SAKINAH DAN SIBALIPARRIQ DALAM PENCEGAHAN KEKERASAN DALAM RUMAH TANGGA (KDRT) - Muhammad Fadel; Achmad Abubakar; Hasyim Haddade (Qolamuna : Jurnal Studi Islam, 2023)
This study aims to identify the implementation of the concept of sakinah and sibaliparriq families in the prevention of domestic violence. This research is a type of library research, namely research whose object of study uses library data in the form of books as the data source. This research was conducted by reading, studying, and analyzing various existing literature, in the form of the Qur'an, hadith, books, and the results of existing research. This study uses a qualitative research approach, which is a systematic research that is used to examine or examine an object in a natural setting without any settlement in it and without testing the hypothesis. From this study there are findings that the implementation of the concept of the sakinah and sibaliparriq family in the prevention of domestic violence in domestic life includes, establishing good communication, husband and wife and children must obey Allah SWT, husband and wife are responsible for providing peace, tranquility, tranquility, and love. affection and love for family, because the sakinah family is a family that is able to carry out Allah's commands as well as possible and stay away from all His prohibitions. Providing religious education to children by delivering them to seek useful knowledge and directing them for the good of others.